Cytomegalovirus Infection During Pregnancy: Where Are We Now? - Ferreira, Marta Fontes; Pereira, Hugo; Cardoso, Olga Couto; Oliveira, Clara; Pereira, Mariana Costa; Couto, Juliana (Gazeta Médica, 2022)
Cytomegalovirus infection is the most frequent congenital infection worldwide, with a prevalence of 1.1% in Mainland Portugal. Fetal infection may present with important manifestations, being the main cause of non-hereditary sensorineural hearing loss in childhood and may also lead to congenital defects of multiple organ systems. The proposal for universal preconception screening has been debated for several years, but there is still no consensus on the subject. Recent data suggest that valacyclovir may be an effective and safe treatment, which may provide a further argument in favor of universal cytomegalovirus screening. This review article seeks to systematize the most recent information on maternal and fetal cytomegalovirus infection, its diagnosis, and possible treatments, as well as to reflect on the relevance of screening before and throughout pregnancy.